SISTEM INFORMASI PT. FORTUNA PROPERTINDO INDONESIA BERBASIS WEB: WEB, MARKETING, PROPERTY, PT. FORTUNA PROPERTINDO INDONESIA - Mulyati, Sri; Fitriyani, Ririn (LP2M STMIK Nurdin Hamzah Jambi, 2020)
PT. Fortuna Propertindo Indonesia as one of the companies engaged in the property sector should be able to utilize information technology in supporting various activities. Marketing carried out by PT. Fortuna Propertindo Indonesia is not conducted at any time, marketing is done by adjusting the work schedule of employees or when the booth is opened. Another problem is that a marketing employee can only serve one prospective buyer at any time. So, stand visitors must wait to be able to talk to the marketing employee if he is giving information to other prospective buyers. This of course caused a feeling of discomfort to the stand visitors. The purpose of this research is to make it easier for customers to find housing that is possible by displaying the type of house, house price, and housing location. The analytical method used is descriptive method and for the design method in this study using diagrams, designing interfaces to coding and databases using PHP, MySql, and Jquery, with the existence of a Housing Marketing Information System it is expected to help expand marketing reach to various regions and increase turnover sales of PT. Fortuna Propertindo Indonesia.